Alih Fungsi Lahan Pertanian Berpengaruh pada Lingkungan Hidup dan Ketahanan Pangan di Indonesia - Widyawati Boediningsih; Suparman Budi Cahyono (Fakultas Hukum Universitas Gresik, 2023)
Indonesia will hold the presidency of the Group of Twenty (G20) in 2022. That was the first time Indonesia was elected as the holder of the G20 presidency, since the G20 was formed in 1999. Indonesia will play a role in determining priority agendas and leading a series of G20 meetings, including the summit to be held in November 2022 in Bali. Financial route priority agenda in the G20 Indonesia 2022 Presidency. Discusses how the G20 protects countries that are still heading for economic recovery (especially developing countries) from the spillover effects of exit policies implemented by countries that recover their economies first (generally developed countries). Indonesia will add to the discussion on the latest global issue, namely food security. Food security is the goal of Indonesia to meet all the food needs of all its residents, with the fulfillment of all food needs of the Indonesian population being able to move, live healthy, and work productively. Food security is very important because it is the key to national economic development and is a basic human need to be fulfilled. The problem of food security is closely related to economic stability (particularly inflation), aggregate economic production costs (cost of living) and national political stability. This can be related to the phenomenon in Indonesia related to the conversion of agricultural land, why is that because food agricultural land is part of the cultivation function land whose existence is currently threatened for other needs such as housing, industry and so on. Thus, the method used to analyze these problems is a qualitative method which explains in depth in connection with the conversion of agricultural land to the effect on the environment and food security in Indonesia.